Strand 2: A Collaborative, Networked University: Organisational and pedagogical challenges - Haugen, Harald; Ask, Bodil (Proceedings of the International Conference on Networked Learning, 1998)
Information- and communication-technology (JCT) as a basis for open and distributed learning (ODL) is rapidly gaining importance as means of providing lifelong learning. Internet and WWW challenge higher education to re-think traditional, academic ways of organising universities and colleges, as well as requiring new pedagogical approaches to the provision of knowledge. Some institutions have found it worth while to join forces in a networked university, sharing responsibilities and supporting one another. Through different projects several links have been established for collaborative actions that are now taking place. This paper will present organisational and pedagogical arrangements chat are necessary when four Norwegian institutions decided to establish a national, networked university - open also for other institutions to join in. Among the organisational aspects, attention is drawn to institutional characteristics, commitment and objectives related co national and international goals and joint activities within education and research. Resources allocated for objectives like economical, technical, professional and pedagogical reorganisation, are specified in a partner contract - signed at the highest level of authority for each partner institution. Concerning pedagogical aspects, discussions have focused on professional collaboration between university researchers and teaching staff for the development of ICT based learning environments. Different pedagogical models like traditional distance education, ICT supported, problem based learning, professional exchange and sharing of results and collaborative learning where students share responsibility for support and learning activities, have been tested. Experiences with these models and combinations of them will be discussed in relation to the function of an ICT based, networked university - or a virtual learning institute (VLI).